Microbial Corrosion Resistance of Stainless Steels for Marine Energy Installations - Machuca, L.; Bailey, Stuart; Gubner, Rolf (Trans Tech Publications Inc, 2011)
A range of stainless steels has been investigated for resistance to microbiologically influenced corrosion in seawater. The corrosion potential was monitored for stainless steel coupons exposed to sterilized seawater and to microbiologically active seawater, which showed the effect of the growth of microorganisms. Cyclic potentiodynamic polarization scans confirmed that 13%Cr stainless steel is very susceptible to localized corrosion under these conditions. 316L stainless steel was also quite susceptible to localized corrosion, whereas 2205 duplex stainless displayed good resistance to localized corrosion. Naturally occurring microorganisms in the seawater were shown to exacerbate the localized corrosion.